2016
DOI: 10.1037/cdp0000066
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and sexual precursor behaviors in Mexican American preadolescent girls: The role of psychological distress, sexual attitudes, and marianismo beliefs.

Abstract: This study underscores the importance of psychological distress in the perceived discrimination and sexual precursor link as well as the compensatory aspects of marianismo against sexual precursor behaviors in Mexican American preadolescent girls. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…The majority of research investigating views of female virginity in Latino adolescents is conducted within the context of adolescent sexuality. Sanchez, Whittaker, Hamilton, and Zayas (2016) investigated the relationship between virtuousness/chastity and sexual behaviors and attitudes among Mexican American middle-school girls. They found negative correlations between views of virtuousness/chastity and attitudes regarding sexual behaviors, and actual sexual precursor behaviors (e.g., spending time alone with a boy, romantically kissing).…”
Section: Views Of Female Virginitymentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of research investigating views of female virginity in Latino adolescents is conducted within the context of adolescent sexuality. Sanchez, Whittaker, Hamilton, and Zayas (2016) investigated the relationship between virtuousness/chastity and sexual behaviors and attitudes among Mexican American middle-school girls. They found negative correlations between views of virtuousness/chastity and attitudes regarding sexual behaviors, and actual sexual precursor behaviors (e.g., spending time alone with a boy, romantically kissing).…”
Section: Views Of Female Virginitymentioning
confidence: 99%
“…Similar associations were established by Espinosa-Hernandez, Vasilenko, and Bámaca-Colbert (2015), who found that views of female virginity were negatively associated with making out, oral sex, and vaginal sex in a sample of adolescents in Mexico. Although romantic relationship status was not assessed in either of the aforementioned studies, it is likely that adolescents who endorse views of female virginity are more inclined to abstain from engaging in sexual behaviors within the context of a romantic relationship (Sanchez et al, 2016). Guilamo-Ramos and colleagues (2009) posited that Latino (i.e., Puerto Rican, Dominican, and Mexican) adolescents seek out romantic partners who endorse similar cultural values.…”
Section: Views Of Female Virginitymentioning
confidence: 99%
See 1 more Smart Citation
“…In response to reports of increased substance use among Latina adolescents, a number of studies have examined substance use etiology and risk factors in this population (Chen & Jacobson, 2012; Elkington, Bauermeister, & Zimmerman, 2010; Gil, Wagner, & Tubman, 2004; Williams & Chang, 2000). In particular, low-income Latina youth often contend with limited resources related to economic disadvantage (Booth & Anthony, 2015; Johnston, O’Malley, Bachman, & Schulenberg, 2013), racial/ethnic discrimination (Sanchez, Whittaker, Hamilton, & Zayas, 2015), and increased exposure to violence and/or criminality (Fagan, Wright, & Pinchevsky, 2014). In addition, Latina youth are at risk for a multitude of psychological stressors related to culture-specific challenges, such as acculturative stress and intergenerational conflict (Phinney, Ong, & Madden, 2000; Kessler, Avenevoli, & Merikangas, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, an often overlooked difficulty is not only meeting the language/dialect needs of the heterogeneous Latino population and finding measures that have been validated in the general or specific Latino population(s) but also ensuring that measures reflect culture, values, and beliefs of participants from heterogeneous Latino groups (Sue & Dhindsa, ). Furthermore, researchers of sexual activity, HIV/AIDS, and substance use among Latinos have cited challenges in recruitment and participation because of cultural mistrust; values such as marianismo , a gender value that reflects both positive and negative dimensions of Latina femininity and familial hierarchy (Sanchez, Whittaker, Hamilton, & Zayas, ); and stigma (Tucker et al, ). Researchers have attempted to overcome these challenges by suggesting or implementing noteworthy practices such as multistep translation methods, pilot‐testing questionnaires with ethnically diverse Latino groups, and thorough training of interviewers in cultural sensitivity (e.g., Herman et al, ).…”
mentioning
confidence: 99%